Effect of Cryoprotectant Concentration on Starter Culture Viability Sinbiotic Yogurt with Freeze Dried Sweet Potato Extract Supplementation - Agustina Intan Niken Tari; Catur Budi Handayani; Sri Hartati (Universitas PGRI Semarang, 2020)
Synbiotic yogurt with purple sweet potato extract supplementation as prebiotics and Lactobacillus plantarum Dad 13 isolated from buttermilk as probiotics has potential as functional food, but requires low storage temperatures. The freeze drying technique requires cryoprotectant as a protective material for products such as yogurt. The purpose of this study was to determine the effect of sucrose concentration on the level of viability of Lactic Acid Bacteria and Lactobacillus plantarum. This study used a Completely Randomized Design with one factor : concentration of sucrose as cryoprotectant: 0%, 2.5%, 5%, 7.5%, and was carried out in three replications. The results showed that the concentration of sucrose significantly affected the yield of freeze dried synbiotic yogurt, total Lactic Acid Bacteria (LAB) after freeze drying, and total Lactobacillus plantarum before and after freeze drying, but did not significantly total amount of LAB before freeze drying. The best treatment, shown in frozen dried synbiotic yogurt with a sucrose cryoprotectant concentration of 5%. The treatment has the following characteristics: yield, 14.797%, total Lactic Acid Bacteria 1.98x 109 CFU / ml before freeze drying, 9.28x 108 CFU / ml after freeze drying, total Lactobacillus plantarum 8.23 x 108 CFU / ml before freeze drying and 6.81 x 108 CFU / ml after freeze drying.